Behavioral evaluation of BALB/c (Mus musculus) mice infected with genetically distinct strains of Toxoplasma gondii. (January 2019) - Bezerra, Elizama C. Machado; dos Santos, Sérgio V.; dos Santos, Talita C. Coelho; de Andrade, Heitor Franco; Meireles, Luciana R.
Abstract: In relation to behavioral changes in rodents infected with Toxoplasma gondii ( T. gondii ), it is believed that the genotype of the infecting strain can have some influence. In this sense, the present work has sought to evaluate the effect of chronic infection by genetically distinct cystogenic strains of T. gondii on the behavior of mice. For this, experimental models of infection with ME-49 (type II) and VEG (type III) strains were developed in isogenic BALB/c mice. ELISA test was performed to evaluate the humoral immune response and real-time PCR test to quantify parasites in the CNS. Behavioral tests such as passive avoidance, open-field and Y-maze tests were also used for, respectively, evaluation of learning and memory, locomotor activity and aversion to feline odor. The results showed that mice infected with VEG strain had higher total IgG level of anti-toxoplasma, higher tissue burden of T. gondii in the CNS, reduction in the long-term memory, lower activity (mobility) and lower aversion to cat urine andl -felinine than mice infected with ME-49 strain. The results suggest that different T. gondii genotypes have a differential impact on behavioral changes in infected mice. Highlights: The mice infected with VEG strain had more prominent behavioral changes. Mice infected with VEG strain had higher anti-toxoplasma antibodies. VEG-infected animals had a higher parasitic load in the CNS.